Food Rx: Integrating horticulture research to improve nutrition and health - Christopher C. Gunter; Danielle D. Treadwell; Marcio F. R. Resende; Vance M. Whitaker; Kelly M. Balmant; Karla P. Shelnutt; Peggy R. Borum; Juan E. Andrade; Renée Goodrich-Schneider; Angelina V. Bernier; William T. Donahoo; Michael S. Jaffee; et al. (Proceedings of the National Academy of Sciences, 2025)
It is clear that the escalating epidemic of insulin resistance and type 2 diabetes has reached a crisis level in the United States, that overweight and obesity are drivers, and that diets and the food system have major roles. It is also clear that nutrition and medical research point to increased healthful fruit and vegetable intake as a key part of any strategy to manage the crisis. But although increasing healthful intake entails both expanding production of fruits and vegetables and improving their healthful characteristics, horticulture has generally been sidelined or taken for granted when strategies are envisioned. This article makes the case that horticulture research and practice can and should be equal partners with nutrition and medicine in the pressing search for effective crisis-management strategies. To do so, it first “runs the numbers” for the scale of the crisis, for trends in fruit and vegetable intake and production, for the scant federal support for horticultural crop production and research, and for horticulture research’s high return on investment. The article then sketches a roadmap to integrate horticulture research and community outreach with nutrition and healthcare, stressing new opportunities. The goal is a US food system that i) makes healthful fruits and vegetables accessible, affordable, and appealing for all and ii) complements a healthcare system spanning patient-based to population-based nutrition.